A Region-Based Approach to Destination Management: “Discover the Euphrates” Case - Aladağ, Münire Tuğba Erdem; Ata, Ahmet Yıldıray (Arif YILDIZ, 2024)
This study examines the relationship between destination management and regional development through Fırat Development Agency's (FKA) “Discover Fırat” program. Destinations are geographical areas where service providers, public institutions and supporting sectors are clustered to offer tourists the experiences they expect. Most tourism activities take place in these areas, which is why destinations gain importance as the basic unit of analysis in tourism research. Destination management is a strategic approach that aims to increase the attractiveness of the region in terms of tourism and provide competitive advantages by managing the tourism resources of the region in a sustainable manner. In this context, this study evaluates the strategies and challenges faced by Fırat Development Agency within the framework of regional destination management and analyzes the solutions obtained in this process. This case study research aims to contribute to the academic literature on destination management and regional development and provide valuable insights for policy makers, business leaders and community stakeholders. The findings highlight the contribution of destination management to regional development and the importance of strategic management for sustainable tourism.

Bu çalışma, destinasyon yönetimi ve bölgesel kalkınma arasındaki ilişkiyi Fırat Kalkınma Ajansı’nın (FKA) "Fırat’ı Keşfet" programı üzerinden incelemektedir. Destinasyonlar, turistlere bekledikleri deneyimleri sunan hizmet sağlayıcıları, kamu kurumları ve destekleyici sektörlerin kümelendiği coğrafi alanlardır. Turizm faaliyetlerinin çoğu bu alanlarda gerçekleşir, bu nedenle destinasyonlar turizm araştırmalarında temel analiz birimi olarak önem kazanmaktadır. Destinasyon yönetimi ise, bölgenin turizm kaynaklarını sürdürülebilir bir şekilde yöneterek, bölgenin turizm açısından çekiciliğini artırmayı ve rekabetçi avantajlar sağlamayı hedefleyen stratejik bir yaklaşımdır. Bu bağlamda çalışmada, Fırat Kalkınma Ajansı’nın bölgesel destinasyon yönetimi çerçevesinde uyguladığı stratejiler ve karşılaştığı zorluklar değerlendirilerek, bu süreçte elde edilen çözümler analiz edilmektedir. Vaka çalışması yöntemiyle yürütülen bu araştırma, destinasyon yönetimi ve bölgesel kalkınma konusundaki akademik literatüre katkı sağlamayı ve politika yapıcılar, iş dünyası liderleri ve toplum paydaşları için değerli içgörüler sunmayı amaçlamaktadır. Elde edilen bulgular, destinasyon yönetiminin bölgesel kalkınmaya olan katkısını ve sürdürülebilir turizm için stratejik yönetimin önemini vurgulamaktadır.
DESTİNASYON YÖNETİMİNE BÖLGE TEMELLİ YAKLAŞIM: "FIRAT'I KEŞFET" ÖRNEĞİ
Keywords: Tourism (Other); Turizm (Diğer)